SOCIO-ECONOMIC INFRASTRUCTURE AND INDUSTRIAL SECTOR OUTPUT IN NIGERIA - Nweke, Onyinyechi; Wasurum, Edward (International Journal of Allied Research in Economics (IJARE), 2023)
This work examined the social infrastructure expenditures and manufacturing sector performance in Nigeria. It specifically examined the relationship between education infrastructure expenditure, health infrastructure expenditure, utility infrastructure expenditure, transportation infrastructure expenditure, and manufacturing sector performance. Relying on the characteristics of the series under investigation, the study adopted autoregressive distributed lag (ARDL) approach to econometric analysis with annual time series data sourced from the CBN Statistical Bulletin, National Bureau of Statistics (NBS), World Bank Development Indicators for the period of 24 years (1996-2019). The study revealed that utilities infrastructure and health infrastructure promote manufacturing sector, while transportation infrastructure reduces industrial output in Nigeria. The study recommended that social infrastructure expenditures should always be given adequate attention as it boosts the activities of the manufacturing sector towards positive and significant output